Complementary Currencies as a Socio-Technical Innovation. Evidence from a local clearing union in Italy - Marco Fama (Coordinamento SIBA, 2020)
The paper points out the importance of considering how the technical solutions adopted in the development of a complementary currency (CC) are related to all the other ingredients required for the establishment of a monetary institution. In particular, the authors aim to shed light on the social implications deriving from the choice to adopt a specific monetary architecture, and how this choice interacts with the other institutional conditions of economic transactions. In doing so, they present the results of empirical research on a clearing-based currency project, showing that monetary tools are likely to produce effects which, far from being a smooth projection of pre-existing social dynamics, are the result of a dialectical process that is also influenced by the way they are technically designed. Even in the case of top-down CC projects, new forms of sociality can emerge from a process of "learning by doing", where monetary innovations serve as a laboratory allowing its users to experiment new ways of combining social and economic interactions. For this to happen, currency projects must be sustained by a whole set of relational, educational and economic resources, but the way they are technically designed deeply affect the conditions required for their institutionalisation.